Hubungan Status Gizi dengan Usia Menarche pada Siswi SMP Kabupaten Ngada - Aurelia Noa; Marselinus Laga Nur; Daniela L. A. Boeky (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2024)
Menarche is an important sign for a woman because it indicates normal hormone production made by the hypothalamus and then passed on to the ovaries and uterus. Late menarche can cause reproductive health problems in women. This study focuses on understanding the relationship between nutritional status and late menarche, which is still a major problem in adolescent reproductive health issues. This study aims to determine the relationship between nutritional status and age of menarche among junior high school students in Ngada Regency in 2023. The type of research used was an analytic survey with a research design using a Case-Control Study approach. The sample in this study was 94 female students, who were divided into 47 female students who experienced late menarche and 47 female students who experienced normal menarche among junior high school students in Ngada Regency. The analysis data used was  univariate, bivariate, and odds ratio with the chi-square test. The results showed that those who had a relationship with the incidence of menarche were parents' income (p = 0.023), body mass index (p = 0.002) and food consumption patterns(p = 0.000). In contrast, psychological conditions had no relationship with the incidence of menarche in junior high school students, with a p-value = 0.168. Factors associated with the incidence of menarche are parents' income, nutritional status as measured using BMI and food consumption patterns as measured through the food frequency forum.